The Effect of the Semiconductive Screen on Space Charge Suppression in Cross-Linked Polyethylene - 李琳 宋伟 王暄 雷清泉 (Chinese physics letters, 2014)
The space charge distributions of cross-linked polyethylene （XLPE） with Borouge＇s BorlinkTM semiconductive screen type LE0550 and LE0595 from a pulsed electro-acoustic method are obtained. The contact interface morphology at the semiconductive screen and the structure of XLPE near the interface are characterized. The dielectric spectrum and the conductivity current of XLPE with the different semiconduetive electrodes are com- pared. The semiconduetive screen changes the structure and the dielectric characteristic of XLPE near the contact interface, which may be the main reason for space charge suppression in XLPE with Borouge＇s type LEO550 semiconduetive screen.